POTENSI PEMBANGKIT LISTRIK TENAGA MIKROHIDRO DENGAN TURBIN KAPLAN PADA SUNGAI MAMBAL - Dwi Lasmana, I Kadek Oki; Indra Partha, Cokorda Gede; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2023)
The Kaplan turbine is a type of reaction turbine that utilizes potential energy to generate motion energy. The Kaplan turbine is very suitable for use in places where the head is low but requires a large discharge. Currently Kaplan turbines are still very little used in Indonesia, especially in Bali. So that it is difficult to obtain specification data relating to Kaplan turbines. Many prototypes are made on a laboratory scale to get maximum results. This study discusses the results of the output voltage, current, power, and efficiency that can be produced by a PLTMH prototype using a Kaplan turbine. This study also discusses the analytical study of the existing hydropower potential, namely, the water flow rate and the height of the water fall (head) of the Mambal River water flow. This prototype test uses a water flow rate of 6 L or 0.006 m^3/s with a guide vane angle of 30 º and a total of 5 runner blades. In the no-load test, the average turbine rotation before being coupled to the generator was 556 rpm, the average turbine rotation after being coupled was 353 rpm. The average result of the largest turbine rotation is 303 rpm, the largest generator rotation result is 499 rpm, the largest generator voltage average result is 5.60 volts, the largest average generator current result is 0.61 Ampere, the result the largest average generator power Key Words : Prototype of PLTMH, Kaplan Turbine, Water Discharge, Output produced is 1.93 Watt, the largest torque is 0.14 Nm, the largest PLTMH efficiency is 5.1%.